PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS (MPLB) 1 DALAM MENANGANI SURAT/DOKUMEN KANTOR DENGAN MENGGUNAKAN KARTU KENDALI DI SMK NEGERI 1 KOTA TASIKMALAYA - Susantini, Santi (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to find out whether the application of the role playing learning model in handling office letters/documents using control cards can improve student learning outcomes, especially class X MPLB 1 at SMK Negeri 1 Tasikmalaya City. This classroom action research was carried out for approximately 3 months, starting from August 18 2022 to October 6 2022 involving 33 students as research subjects. The data collection techniques used by researchers were observation, tests and documentation carried out over 2 cycles. Each cycle consists of 5 stages, namely: 1) Action planning, 2) Action implementation, 3) Action observation, and 4) Reflection. Based on the results of the research that has been carried out, it can be concluded that the use of the role playing method in learning activities for handling incoming and outgoing mail has a very positive influence on student learning outcomes. This can be seen from the results of observations which show data that 78.2% of the tasks of handling incoming mail can be performed well by students, and 82.5% of all tasks of handling outgoing mail can be performed well by students. Then in the next cycle, almost all tasks in the procedures for handling incoming and outgoing mail using the control card system were successfully carried out by students very well, with a percentage of 92.9% for incoming mail and 94.7% for handling outgoing mail using the card system. control. Meanwhile, for student learning outcomes in the field of knowledge, the role playing method really helps students. Before implementing the role playing method, only around 6.1% of students got the minimum completeness score in handling incoming and outgoing mail using control cards or only 2 students out of 33 students in class X Office Management and Business Services (MPLB) 1. After applying the role playing method in cycle I, students who achieved the minimum completeness score began to increase, namely around 47.2% and after applying the role playing method in cycle II, almost all students were finally able to achieve the minimum completeness score, namely 88%.